Dermatofibroma simulating seborrheic keratosis dermoscopically - Daniel Holanda Barroso; Camila Pinon Zoby Leite; Gabriela Diniz de Souza Araujo; Márcia Almeida Galvão Teixeira; Eliane Ruth Barbosa Alencar; Silvana Maria de Morais Cavalcanti (Sociedade Brasileira de Dermatologia, 2016)
Abstract: Dermatofibroma is a frequent benign tumor of easy clinical diagnosis in most cases, but that can mimic other dermatoses. Dermoscopy may help to define the diagnosis and its classical pattern is a central white area, similar to a scar, surrounded by a discrete pigment network. However, dermoscopic findings are not always typical. We describe here a case of dermatofibroma exhibiting ridges, furrows and pseudocomedos, a pattern which is typical of seborrheic keratosis, in dermoscopy.